Gambaran Stabilitas Pooled plasma CPDA Sebagai Bahan Kontrol Kualitas Pemeriksaan Asam Urat Pada Uji Presisi Within run dan Between day - Setyaji, Yoki; Duri, Iin Desmiany; Setyowatiningsih, Lilik (Jaringan Laboratorium Medis, 2024)
The quality of laboratory test results is ensured by implementing quality control measures, which usually require control materials. The high cost of commercial control materials poses a challenge for laboratory quality control. Commonly, laboratory control materials are commercial control serums derived from animal serum that undergoes lyophilization during manufacturing. This study aims to assess the stability of CPDA pooled plasma that has been frozen for 60 days, using precision tests both within-run and between-day. Methods: This experimental research utilized CPDA pooled plasma samples from hematology laboratory waste at Poltekkes Kemenkes Semarang. The samples were frozen at -20â„ƒ for 60 days. Quality control (QC) analysis was conducted using within-run and between-day precision tests without replication, to determine the standard deviation (SD) and coefficient of variation (CV). The results were then statistically analyzed using a one-way ANOVA to assess the difference in CPDA pooled plasma stability between the within-run and between-day precision tests. The QC results for within-day and between-day precision were as follows: the average for within-day was 4.066 and for between-day 3.2785; SD for within-day was 0.20 and for between-day 0.09; CV for within-day was 4.9% and for between-day 2.9%. The one-way ANOVA test showed a significance value of 0.316, indicating no significant difference between the within-day and between-day QC methods in terms of precision testing. Conclusion: CPDA pooled plasma remains stable in maintaining the precision of QC results for uric acid using the enzymatic colorimetric method (end-point) after 60-80 days of storage and can be used as an alternative to commercial control materials in uric acid QC testing.